2014
DOI: 10.2527/jas.2014-7880
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protein and fat concentration in coproduct-based growing calf diets on performance and carcass composition

Abstract: Angus×Simmental crossbred heifers (n=150) and steers (n=100) were used to evaluate 1 of 5 growing diets: 1) a corn-based growing diet (CRN); 2) a high-fat, high-protein coproduct blend; 3) a high-fat, low-protein coproduct blend; 4) a low-fat, high-protein coproduct blend; and 5) a low-fat, low-protein coproduct blend in a 2×2+1 factorial arrangement. Low-protein and low-fat diets were formulated to be isonitrogenous and isofat to CRN (16.0% CP and 3.0% fat), and high-protein and high-fat diets were formulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Meteer et al (2012) observed no differences in ADG in early-weaned calves fed either starchor coproduct-based growing diets, but in that study, calves consuming coproduct diets consumed 0.88 kg/d more than calves fed starch-based diets. Segers et al (2014) noted increased ADG in cattle fed corn during the growing phase but increased DMI in cattle fed coproducts when comparing coproduct-based diets to corn-based diets. Segers et al (2014) also observed no difference in final BW.…”
Section: Methodsmentioning
confidence: 94%
See 4 more Smart Citations
“…Meteer et al (2012) observed no differences in ADG in early-weaned calves fed either starchor coproduct-based growing diets, but in that study, calves consuming coproduct diets consumed 0.88 kg/d more than calves fed starch-based diets. Segers et al (2014) noted increased ADG in cattle fed corn during the growing phase but increased DMI in cattle fed coproducts when comparing coproduct-based diets to corn-based diets. Segers et al (2014) also observed no difference in final BW.…”
Section: Methodsmentioning
confidence: 94%
“…Segers et al (2014) noted increased ADG in cattle fed corn during the growing phase but increased DMI in cattle fed coproducts when comparing coproduct-based diets to corn-based diets. Segers et al (2014) also observed no difference in final BW. These data indicate that because corn-based diets are more energy dense, they tend to produce higher gains and limit DMI compared with coproducts such as distillers' grains or corn gluten feed; however, in the current study, DMI was not different between CNT and 10% CDS.…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations